A Multiscale Approach to Blast Neurotrauma Modeling: Part II: Methodology for Inducing Blast Injury to in vitro Models - Effgen, Gwen B.; Hue, Christopher D.; Vogel, Edward; Panzer, Matthew B.; Meaney, David F.; Bass, Cameron 'Dale' R.; Morrison, Barclay (Frontiers in Neurology, 2012)
Due to the prominent role of improvised explosive devices (IEDs) in wounding patterns of U.S. war-fighters in Iraq and Afghanistan, blast injury has risen to a new level of importance and is recognized to be a major cause of injuries to the brain. However, an injury risk-function for microscopic, macroscopic, behavioral, and neurological deficits has yet to be defined. While operational blast injuries can be very complex and thus difficult to analyze, a simplified blast injury model would facilitate studies correlating biological outcomes with blast biomechanics to define tolerance criteria. Blast-induced traumatic brain injury (bTBI) results from the translation of a shock wave in air, such as that produced by an IED, into a pressure wave within the skull-brain complex. Our blast injury methodology recapitulates this phenomenon in vitro, allowing for control of the injury biomechanics via a compressed-gas shock tube used in conjunction with a custom-designed, fluid-filled receiver that contains the living culture. The receiver converts the air shock wave into a fast-rising pressure transient with minimal reflections, mimicking the intracranial pressure history in blast. We have developed an organotypic hippocampal slice culture model that exhibits cell death when exposed to a 530  17.7 kPa peak overpressure with a 1.026 ± 0.017 ms duration and 190 ± 10.7 kPa-ms impulse in-air. We have also injured a simplified in vitro model of the blood-brain barrier, which exhibits disrupted integrity immediately following exposure to 581  10.0 kPa peak overpressure with a 1.067 ms ± 0.006 ms duration and 222 ± 6.9 kPa-ms impulse in-air. To better prevent and treat bTBI, both the initiating biomechanics and the ensuing pathobiology must be understood in greater detail. A well-characterized, in vitro model of bTBI, in conjunction with animal models, will be a powerful tool for developing strategies to mitigate the risks of bTBI.